QUALITATIVE PHYTO CHEMICAL ANALYSIS OF SEED AND LEAF CALLUS EXTRACTS OF CANTHIUM PARVIFLORUM LAM. GUNTUR DISTRICT, ANDHRA PRADESH. - S.CHANDRA KALA; K. MALLIKARJUNA; P.ARUNA (International Journal of Pharma and Bio Sciences, 2012)
Generally the medicinal plants consist of more phytochemicals and all of them are secondary metabolites. These phytochemicals have the ability to produce physiological changes on the human body. The phytochemicals have various complex substances. Keeping this view in mind the present investigation was carried out in Canthium parviflorum seed material in comparison with in-vitro leaf callus material. Qualitative phytochemical analysis of these materials confirms the presence of various phytochemicals. The presence of terpenoids, saponins, steroids, tannins, quinones and gums in leaf callus was observed. The wild seed extracts contain terpenoids, phenols, saponins, gums, oils and quinones. The present preliminary phytochemical analysis may form the basis for drug development in future using the whole plant or parts of Canthium parviflorum.